Lazarus rising / John Howard. - Howard, John, 1939- (HarperCollins, 2010)
The account of a 30 year political career, this is also the autobiography of the youngster who was born at the start of WWII, who studied extra hard to overcome serious deafness and who latched onto the family passion for current affairs and politics.